Pembayaran Fee Kurator dalam Hal Putusan Pernyataan Pailit Dibatalkan Oleh Mahkamah Agung - Andani, Devi (Kertha Patrika; Vol 44 No 2 (2022), 2022)
This study aims to determine the payment of the curator's fee in the event that the decision of the bankruptcy statement is canceled by the Supreme Court so that it can examine and find out how the payment of the curator's fee in the event that the decision of the bankruptcy statement is annulled by the Supreme Court, as well as to examine and find out the legal consequences of the curator's actions in the event that the decision of the bankruptcy statement is canceled. by the Supreme Court. This research is a type of qualitative research by following the typology of normative legal research. Research data were collected by means of literature and document studies. The data that has been collected will be identified and compiled systematically, both data obtained from primary legal materials, secondary legal materials, and tertiary legal materials. Then all the data obtained from the literature study and document study are relevant to the related theory and written descriptively and analyzed qualitatively. The results of this study show that: first, based on the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia (Permenkumham) Number 18 of 2021 concerning Guidelines for Service Fees for Curators and Management in Article 3 paragraph (1) letter c, payment of the curator fee in the case of a statement decision bankruptcy is canceled by the Supreme Court either at the level of cassation or review, then the amount of service fees is charged to the applicant for the declaration of bankruptcy or the applicant and debtor, the amount of which is determined by the Panel of Judges. Second, the decision to declare bankruptcy was canceled by the Supreme Court either at the level of cassation or review, then the legal consequences that occur are in accordance with the provisions of Article 72 of the Bankruptcy Law and PKPU, namely the curator is responsible for errors or omissions in carrying out management and/or settlement tasks. cause loss to the bankruptcy estate. The legal consequence is the responsibility of the curator after the decision of the Supreme Court that annuls the bankruptcy decision, namely all legal actions that have been carried out by the curator in managing and settling the bankruptcy estate cannot be restored to their original state and are binding forever.